2017
DOI: 10.1038/s41598-017-06650-w
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling heme detoxification in the malaria parasite by in situ correlative X-ray fluorescence microscopy and soft X-ray tomography

Abstract: A key drug target for malaria has been the detoxification pathway of the iron-containing molecule heme, which is the toxic byproduct of hemoglobin digestion. The cornerstone of heme detoxification is its sequestration into hemozoin crystals, but how this occurs remains uncertain. We report new results of in vivo rate of heme crystallization in the malaria parasite, based on a new technique to measure element-specific concentrations at defined locations in cell ultrastructure. Specifically, a high resolution co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…Plasmodium uses a system to detoxify heme (Fe 3+ ) called biocrystallization based on the formation of hemozoin pigment which appears as a dark black crystalline spot (a dark brown pigment) in red blood cells of infected patients 1418 . Hemozoin is chemically and structurally identical to β-hematin, a heme dimer that crystallizes under the acidic conditions of digestive vacuole of Plasmodium (pH values of 4.8–5.0) 1820 . It contains two heme (Fe 3+ ) monomers reciprocally linked through coordination complexes between the carboxyl group of a propionate side chain of one monomer and the iron (Fe 3+ ) atom in the porphyrin ring of another monomer 19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium uses a system to detoxify heme (Fe 3+ ) called biocrystallization based on the formation of hemozoin pigment which appears as a dark black crystalline spot (a dark brown pigment) in red blood cells of infected patients 1418 . Hemozoin is chemically and structurally identical to β-hematin, a heme dimer that crystallizes under the acidic conditions of digestive vacuole of Plasmodium (pH values of 4.8–5.0) 1820 . It contains two heme (Fe 3+ ) monomers reciprocally linked through coordination complexes between the carboxyl group of a propionate side chain of one monomer and the iron (Fe 3+ ) atom in the porphyrin ring of another monomer 19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The heme is rendered inert by crystallization into hemozoin. We have recently shown that the parasite stores large quantities of hemoglobin in its digestive vacuole (4). For the parasite to survive, the rate of heme liberation via hemoglobin digestion must not exceed the rate of hemozoin crystallization.…”
mentioning
confidence: 99%
“…Such access to the ultrastructural organization in whole cells placed X-ray microscopy as a valuable tool to study cell-parasite interactions. Structural development of malaria parasite, for example, was extensively studied by several groups by 2D soft X-ray microscopy [119121], soft X-ray coherent diffraction imaging }[122] and X-ray fluorescence diffraction [123, 124]. Spatial localization of vaccinia and herpes viral factories was likewise observed by X-ray microscopy [125127].…”
Section: External Morphologymentioning
confidence: 99%